Правові засади організації інклюзивної освіти дітей дошкільного віку - Кузава, Ірина; Kuzava, Irina (Східноєвропейський національний університет ім. Лесі Українки, 2015)
У статті розглянуто особливості організаційної побудови інклюзивної освіти в системі дошкілля. Здійснено дослідження нормативно-правового та організаційно-правового забезпечення інклюзивної освіти дітей дошкільного віку. Встановлено, що чинне законодавство гарантує право на освіту дітей із особливими освітніми потребами на основі рівності можливостей, забезпечуючи спеціальну освіту на всіх рівнях навчання протягом усього життя. Зроблено висновок про здійснення спеціальної роботи щодо підготовки компетентних педагогічних кадрів, створення системи психолого-педагогічного супроводу інклюзивної освіти.The inclusion of people with mental and physical disabilities in the general space is the general global trend, which is typical for highly developed countries and is caused by a change in the attitude of society and the state to this category of citizens of segregation and aggression to tolerance and inclusion. Typically, they are often limited in their communication with the outside world, their peers and adults, in communion with nature, art and more. The article studies the legal principles of the organization of inclusive education of preschool children. The features of the organizational structure of inclusive education in the doshkillya. The investigation regulatory, organizational and legal support inclusive education of preschool children. It is established that the legislation guarantees the right to education of children with special educational needs on the basis of equal opportunity, providing special education at all levels of lifelong learning. In particular, the legislation is a kind of "engine" promote inclusion, which guarantees the right to education of children with special educational needs on the basis of equal opportunity, providing special education at all levels of lifelong learning. However, its implementation in practice requires amendments to existing regulations in the implementation of the inclusive education of children requiring correction of mental and physical development. The priorities of the state policy in the field of the right to education of children requiring correction of mental and physical development is the creation of appropriate conditions for their education based on their mental and physical features, including most early detection of disorders in their development and organization of remedial work with them; create variant conditions for education of preschool children with mental and physical disorders; improvement of the legal framework that regulates the education of preschool children requiring correction of mental and physical development; Adapted create an environment which would ensure full integration and personal self-fulfillment in teaching children with mental and physical disabilities. The conclusion of work on the implementation of the special training of competent teaching staff, a system of psychological and pedagogical support inclusive education.
Legal fundamentals of organization inclusive education for preschool children.
Keywords: діти дошкільного віку; інклюзивна освіта; принципи інклюзивної освіти; право на освіту; preschool children; inclusive education; the principles of inclusive education; the right to education